Study of Reaction Kinetics by Flynn Wall Ozawa Method on Sawdust Pyrolysis Process - Alif Gita Arumsari; Pandit Hernowo; Jemmy Wibowo; Mukhammad Yazid Fadlulloh; Rasino Setiawan (Jurnal Kimia Terapan Indonesia, 2022)
Pyrolysis which is also called thermolysis will chemically decompose organic matter (biomass) through a heating process without or little O2 or other reagents, where the raw material will undergo a breakdown of the chemical structure into a gas phase. The purpose of this study is as an alternative solution in answering the problem of fuel scarcity in everyday life, & Knowing the amount of activation energy calculated using the Flynn Wall Ozawa method. The biomass used is Dutch teak sawdust obtained from the wood furniture industry in the Tangerang area.The experimental results of pyrolysis of Dutch teak sawdust with round gas opening from experiment 1 to experiment 9 obtained BCO as much as 6.00%, 6.50%, 6.83%, 7.33%, 7.67%, 8 ,83%, 10.17%, 14.33%,16.33%. . While the results of the round gas opening experiment from experiment 1 to experiment 9, BCO was obtained as much as5.67%, 6.17%, 6.67%, 7.17%, 7.33%, 7.83%, 9.67%, 13.83%, 15.83%. The pyrolysis process produces three types of products, namely solid products or charcoal, liquid products (bio-oil) & gas. In our research, the best quality bio oil obtained at temperatures from 548 K to 598 K. The results of bio The oil obtained at this temperature is brownish yellow in color, with an average volume of ± 48 g of bio oil (52.6 ml).